Movement Monitoring in Commercial Areas Using Internet of Things - Varela-Aldás, José (2023)
The Internet of Things has been a trend in the last decade and is now found in countless applications, solving problems in almost any field. Specifically, in the commercial area, there is an effort to apply this technology to facilitate the control of services or processes. This work presents the movement monitoring of commercial areas. The proposal uses the ESP32 board that, using passive infrared sensors located perpendicular to each other, covers two areas of interest for commercial premises with multiple products. The collected data travel to the ThingSpeak Platform, where there are graphs with the states of the sensors, allowing identify the active area. The results present the motion state readings in the two areas, indicating the correct functioning of the system. Finally, we use a technology acceptance model to analyze this proposal, determining an acceptance of 69.6% that is not favorable for this proposal.